Due osservazioni sulla metafisica della prescienza (Lebenswelt. Aesthetics and philosophy of experience., 2013)
The paper discusses two problems concerning the metaphysics of foreknowledge. In the first section I focus on an argument that purports to show that there is no such a thing. In the second one I discuss the relation between the foreknowledge of our own behaviour, or ‘autoforeknowledge’, and what we may call ‘the phenomenology of freedom’. As for the first issue, I employ David Lewis’ discussion of the Grandfather Paradox to argue that the argument in question overlooks a key feature of the semantics of ‘can’. As for the second issue, I develop some remarks by Paul Horwich to show that, contrary appearances notwithstanding, autoforeknowledge is not necessarily incompatible with the phenomenology of freedom.